Effect of school lockdown due to the COVID-19 pandemic on screen time among adolescents in Hungary: a longitudinal analysis - Major, David; Fazekas-Pongor, Vince; Pártos, Katalin; Tabák, Adam G.; Ungvari, Zoltan I.; Eörsi, Dániel; Árva, Dorottya; Terebessy, András (Frontiers in Public Health, 2023)
Introduction Studies indicate that due to school lockdown during the Coronavirus Disease 2019 (COVID-19) pandemic, screen time increased more steeply than pre-pandemic years. The aim of our study was to examine changes in screen time and its components (screen time spent on videos, games, homework, and other activities) of adolescents affected by COVID-19 school closures compared to controls from pre-pandemic years and to assess the effect of family structure and family communication. Methods Two sets of ninth-grader boys and girls transitioning into 10th grade were included in the analysis. The ‘pre-COVID classes’ (controls) completed the baseline survey in February 2018 and the follow-up survey in March 2019. ‘COVID classes’ (cases) completed the baseline survey in February 2020 (1 month before the COVID-19-related school lockdowns) and the follow-up survey in March 2021. Linear mixed models stratified by sex were built to assess the change in screen time over one year adjusted for family structure and communication. Results Our study population consisted of 227 controls (128 girls, 99 boys) and 240 cases (118 girls, 122 boys). Without COVID-19, overall screen time did not change significantly for boys, but there was a decrease in screen time for gaming by 0.63 h, which was accompanied by an increase of 1.11 h in screen time for other activities (consisting mainly of social media and communication). Because of the pandemic, all components increased by 1.44–2.24 h in boys. Girls’ screen time and its components remained stable without school lockdown, while it increased for videos and homework by 1.66–2.10 h because of school lockdown. Living in a single-parent household was associated with higher, while better family communication resulted in lower screen time. Discussion Our results indicate that COVID-19-related school lockdowns modified the age-specific increase in screen time for boys and girls as well. This trend, however, may be counterbalanced by improving communication between family members.